A proteomic atlas of the neointima identifies novel druggable targets for preventive therapy. (8th April 2021) - Wierer, Michael; Werner, Julia; Wobst, Jana; Kastrati, Adnan; Cepele, Ganildo; Aherrahrou, Redouane; Sager, Hendrik B; Erdmann, Jeanette; Dichgans, Martin; Flockerzi, Veit; Civelek, Mete; Dietrich, Alexander; et al.
Abstract: Aims : In-stent restenosis is a complication after coronary stenting associated with morbidity and mortality. Here, we sought to investigate the molecular processes underlying neointima formation and to identify new treatment and prevention targets. Methods and results : Neointima formation was induced by wire injury in mouse femoral arteries. High-accuracy proteomic measurement of single femoral arteries to a depth of about 5000 proteins revealed massive proteome remodelling, with more than half of all proteins exhibiting expression differences between injured and non-injured vessels. We observed major changes in the composition of the extracellular matrix and cell migration processes. Among the latter, we identified the classical transient receptor potential channel 6 (TRPC6) to drive neointima formation. While Trpc6 −/− mice presented reduced neointima formation compared to wild-type mice (1.44 ± 0.39 vs. 2.16 ± 0.48, P  = 0.01), activating or repressing TRPC6 in human vascular smooth muscle cells resulted in increased [vehicle 156.9 ± 15.8 vs. 1-oleoyl-2-acetyl-sn-glycerol 179.1 ± 8.07 (10 3 pixels), P  = 0.01] or decreased migratory capacity [vehicle 130.0 ± 26.1 vs. SAR7334 111.4 ± 38.0 (10 3 pixels), P  = 0.04], respectively. In a cohort of individuals with angiographic follow-up ( n  = 3068, males: 69.9%, age: 59 ± 11 years, follow-up 217.1 ± 156.4 days), homozygous carriers of a common genetic variant associated with elevated TRPC6 expression were at increased risk of restenosis after coronary stenting (adjusted odds ratio 1.49, 95% confidence interval 1.08–2.05; P  = 0.01). Conclusions : Our study provides a proteomic atlas of the healthy and injured arterial wall that can be used to define novel factors for therapeutic targeting. We present TRPC6 as an actionable target to prevent neointima formation secondary to vascular injury and stent implantation. Graphical Abstract: